Long-term field operation of photovoltaic solar water pumps. Issue 5 (4th July 2018) - Odeh, Ibrahim; Yohanis, Yigzaw Goshu; Norton, Brian; Alsoud, Mohammed; Odeh, Dina
ABSTRACT: Three-year, hourly averaged, field data have been analysed for eight installed photovoltaic (PV) systems. Correlations of PV array yield as a function of insolation have been developed using long-term field data considering PV as a part of system in which load affects its performance. Another scenario that considered infinite load like that for grid-connected PV system has been investigated and array yield correlations were obtained. Influence of ambient temperature and wind speed on PV array yield is investigated.